2010
DOI: 10.1111/j.1469-7610.2010.02287.x
|View full text |Cite
|
Sign up to set email alerts
|

Very early predictors of conduct problems and crime: results from a national cohort study

Abstract: Risk factors from pregnancy to age 5 are quite strong predictors of conduct problems and crime. New risk assessment tools could be developed to identify young children at high risk for later antisocial behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
1
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(84 citation statements)
references
References 25 publications
3
69
1
7
Order By: Relevance
“…This is consistent with the view that externalizing behaviors are explained more by genes among children raised by parents with more resources and fewer life constraints because environmental risk is minimal in nurturing environments. Though parents with more socioeconomic resources tend to show more positive parenting such as emotional support (Conger et al, 1992;Dodge, Pettit, & Bate, 1994) and these two factors are both negatively correlated with externalizing behaviors (Barry et al, 2005;Keiley et al, 2000;McLoyd & Smith, 2002;Murray et al, 2010;Stormshak et al, 2000), results from the ECLS-B subsample indicate that parental emotional support and SES moderate genetic contributions to externalizing behaviors in different ways. Different patterns of moderation effects by correlated moderators could therefore be a promising factor to consider in future investigation of G × E interactions.…”
Section: Cnlsymentioning
confidence: 99%
See 2 more Smart Citations
“…This is consistent with the view that externalizing behaviors are explained more by genes among children raised by parents with more resources and fewer life constraints because environmental risk is minimal in nurturing environments. Though parents with more socioeconomic resources tend to show more positive parenting such as emotional support (Conger et al, 1992;Dodge, Pettit, & Bate, 1994) and these two factors are both negatively correlated with externalizing behaviors (Barry et al, 2005;Keiley et al, 2000;McLoyd & Smith, 2002;Murray et al, 2010;Stormshak et al, 2000), results from the ECLS-B subsample indicate that parental emotional support and SES moderate genetic contributions to externalizing behaviors in different ways. Different patterns of moderation effects by correlated moderators could therefore be a promising factor to consider in future investigation of G × E interactions.…”
Section: Cnlsymentioning
confidence: 99%
“…Higher SES is consistently associated with lower levels of externalizing behaviors (Barry et al, 2005;Dodge et al, 1994;Keiley et al, 2000;Murray et al, 2010), and this relation is likely to be mediated by more proximal mechanisms. Socioeconomic advantage is not only associated with higher resources, but also with higher quality care provided by individuals in children's immediate environment (Conger et al, 1992;Dodge et al, 1994).…”
Section: Socioeconomic Advantage As a Protective Factormentioning
confidence: 99%
See 1 more Smart Citation
“…Rather, as Klevens et al (2001) have shown, varying combinations of risk factors exacerbate cumulative disadvantages that are linked to the long-term propensity for violent criminal outcomes. The study examines retroactively the extent to which combinations of risk factors produce socially toxic family environments and serve as distal precursors to violent criminality in adulthood (see Murray, et al, 2010).…”
Section: Socially Toxic Environmentsmentioning
confidence: 99%
“…Finally, evidence indicates that behavioural problems in childhood are associated with increased risk in a number of healthrelated areas in adulthood including: obesity, substance misuse, risky sexual behaviour (e.g., multiple partners; teen pregnancy/parenthood), injury, hospitalisation due to road traffic accidents, chronic widespread pain, long-term illness, psychological ill health, mortality (by midlife), and criminal behaviour (von Stumm et al, 2011;Fergusson, Horwood, & Ridder, 2005;Timmermans, van Lier, & Koot 2008;Jokela, Power, & Kivimäki, 2009;Redelmeier, Chan, & Lu, 2010;Pang, Jones, Power, & Macfarlane, 2010;Clark, Rodgers, Caldwell, Power, & Stansfeld, 2007;Jokela, Ferrie, & Kivimäki, 2009;Murray, Irving, Farrington, Colman, & Bloxsom, 2010). Finally, evidence indicates that behavioural problems in childhood are associated with increased risks in a number of health-related areas in adulthood including: obesity (von Stumm, Deary, Kivimäki, et al, 2011), substance misuse (von Stumm, Deary, Kivimäki, et al 2011;Fergusson, Horwood, Ridder, 2005), risky sexual behaviour (e.g., multiple partners; teen pregnancy/parenthood) (Fergusson, Horwood, Ridder, 2005), injury (Jokela, Power, Kivimäki, 2009), hospitalisation due to road traffic accidents (Redelmeier, Chan, Lu, 2010), chronic widespread pain (Pang, Jones, Power, et al, 2010), long-term illness (von Stumm, Deary, Kivimäki, et al, 2011), psychological ill health (Fergusson, Horwood, Ridder, 2005;Clark, Rodgers, Caldwell, et al, 2007), mortality (by midlife) (Jokela, Ferrie, Kivimäki, 2009), and criminal behaviour (Fergusson, Horwood, Ridder, 2005;Murray, Irving, Farrington, et al, 2010).…”
Section: Introductionmentioning
confidence: 99%